Menuju Digitalisasi Berdampak Inklusif di Papua Barat dan Papua Barat Daya: Sebuah Analisis Input-Output Miyazawa - Ahmadi Murjani (Ecoplan, 2025)
Digital transformation is one of the key drivers of economic growth; however, its impact on equitable development in West Papua and Southwest Papua remains underexplored, particularly at the regency level. This study aims to analyze the effects of digitalization on economic output growth and income distribution in West Papua and Southwest Papua using the Miyazawa Input-Output (IO) approach. The model integrates linkages across 17 sectors and households in 13 regencies, enabling the tracing of economic impacts both sectoral and spatial. The data include the West Papua IO Table 2016 updated to 2024, consumption patterns from Susenas, and income distribution from Sakernas. Simulations were conducted through five intervention scenarios involving digitalization alongside the strengthening of Agriculture, Construction, Financial and Insurance Services, Wholesale and Retail Trade, and Transportation and Warehousing, complemented by Theil Index analysis to measure interregional inequality. The results indicate that digitalization, particularly through the empowerment of MSMEs and digital financial services, generates higher output growth compared to other scenarios but tends to widen disparities in most cases. Conversely, scenarios incorporating logistics strengthening show more equitable income distribution across regencies, with significant improvements in areas such as Pegunungan Arfak, Maybrat, and Tambrauw. These findings highlight the importance of integrating digitalization with logistics enhancement to ensure that the benefits of development are distributed more inclusively and evenly.